Countering the ideology of hate : the tripartite approach - Mohamed Nawab Mohamed Osman (2014)
The world was rocked by two terrorist attacks over the past week: one in Kenya by Al-Shabaab which gunned down innocent civilians. The other was in Pakistan when the Tehrik-e-Taliban killed more than 91 Pakistani Christians. Both were inspired by a deviant understanding of Islam. Mainstream Muslims must challenge these misrepresentations of Islam by involving traditional Muslim scholars, Muslim activists and government authorities.